Evolutionary Computation in Combinatorial Optimization 9th European Conference, EvoCOP 2009, T<U+00fc>bingen, Germany, April 15-17, 2009. Proceedings - Cotta, Carlos.; Cowling, Peter. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 9th European Conference on Evolutionary Computation in Combinatorial Optimization, EvoCOP 2009, held in T<U+00fc>bingen, Germany, in April 2009. The 21 revised full papers presented were carefully reviewed and selected from 53 submissions. The papers present the latest research and discuss current developments and applications in metaheuristics - a paradigm to effectively solve difficult combinatorial optimization problems appearing in various industrial, economical, and scientific domains. Prominent examples of metaheuristics are evolutionary algorithms, simulated annealing, tabu search, scatter search, memetic algorithms, variable neighborhood search, iterated local search, greedy randomized adaptive search procedures, estimation of distribution algorithms and ant colony optimization.